Can the diversity of students and differentiated instruction achieve curriculum targets? - Romadani, Moh Nafis Husen (Universitas Negeri Yogyakarta, 2025)
Learning in the 21st century requires a shift from teacher-centred to student-centred methods. This change is necessary to equip students with essential 21st-century skills known as the 4Cs (Communication, Collaboration, Critical Thinking, Creativity). To develop these skills, educators must guide their students, who have diverse characteristics, in mastering the 4Cs. Differentiated instruction is a teaching approach aimed at accommodating students' varied needs, interests, and abilities in a classroom. This approach involves adjusting the content, process, products, and learning environment so that each student can learn most effectively. Differentiated instruction is an ideal concept for students. This approach can enhance students' potential according to their individual learning needs, including their interests, learning readiness, and learning profiles. The purpose of this article is to describe how differentiated instruction can meet the curriculum targets of education in Indonesia. This research is descriptive in nature, involving the collection of various relevant references on differentiated instruction.